Caveolin-1 in renal disease - Sourabh Chand (Scientific Journal of Genetics and Gene Therapy - Peertechz Publications, 2018)
Caveolin-1 is the essential structural formation for lipid raft formation. It has been ascribed to several disease processes in humans due to its ubiquitous distribution. Patients with chronic kidney disease suffer great morbidity and mortality where manipulation of caveolin-1 could lead to new potential therapeutic targets in this patient group. This review highlights caveolin-1 structure, signalling and provides examples of studies of caveolin-1 single nucleotide polymorphism in chronic kidney disease.